Long-Term Follow-up of Multinodular and Vacuolating Neuronal Tumors and Implications for Surveillance Imaging - Dogra, S.; Zagzag, D.; Young, M.; Golfinos, J.; Orringer, D.; Jain, R. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Most multinodular and vacuolating neuronal tumors (MVNTs) are diagnosed and followed radiologically without any change across time. There are no surveillance guidelines or quantitative volumetric assessments of these tumors. We evaluated MVNT volumes during long follow-up periods using segmentation tools with the aim of quantitative assessment.MATERIALS AND METHODS: All patients with MVNTs in a brain MR imaging report in our system were reviewed. Patients with only 1 brain MR imaging or in whom MVNT was not clearly the most likely diagnosis were excluded. All MVNTs were manually segmented. For all follow-up examinations, absolute and percentage volume change from immediately prior and initial examinations were calculated.RESULTS: Forty-eight patients (32 women; median age, 50.5 years at first scanning) underwent 158 brain MRIs. The median duration between the first and last scan was 15.6 months (interquartile range, 5.7-29.6 months; maximum, 6.4 years) and between consecutive scans, it was 6.7 months (interquartile range, 3.3–12.4 months; maximum, 4.9 years). Pearson correlation coefficients between days since immediately prior scan versus absolute and percentage volume change from immediately prior scan were r = 0.05 (P = .60) and r = 0.07 (P = .45), respectively. For the relationship between days since the first scan versus absolute and percentage volume change from the first scan, values were r = –0.06 (P = .53) and r = –0.04 (P = .67), respectively.CONCLUSIONS: MVNT segmentation across follow-up brain MR imaging examinations did not demonstrate significant volume differences, suggesting that these tumors do not enlarge with time. Hence, frequent surveillance imaging of newly diagnosed MVNTs may not be necessary.DNETdysembryoplastic neuroepithelial tumorIQRinterquartile rangeMVNTmultinodular and vacuolating neuronal tumor